How do taxes affect size of shadow economy? : - Megrelidze, Giorgi (2018)
Primary focus of my Bachelor`s Thesis is how taxes affect size of shadow economy. Beginning of my thesis consists of different opinions of prominent economists, public figures and journalists about the Phenomena. I am discussing how those opinions are sometimes similar and sometimes totally different depending on viewpoint and timescale.In Theoretical Part Illicit activities are analysed thru lenses of welfare economy. I am looking at Short run and Long run consequences of increasing Shadow Economy and analyse positive and negative aspects of Illicit activities on wealth of states and its inhabitants. Using Economic Psychology, I am identifying Internal and External Sources that are affecting individual’s decision process including but not limited to rising tax burden, which has already been Identified by many economists as main force behind rising illicit activities. As such Tax burden is discussed in more details using, extended Neo-Classical Income-Leisure Model; While Modified Laffer-Swan model is used at analysing how taxes, unofficial and official economy are interconnecting on macro level.In practical part of my Bachelor`s Thesis I am looking at how Total Tax Wedge on the individual Labourer is correlated with Size of Shadow economy as % of GDP. data for given variables for 32 countries spanning 21 years (1995-2015) is taken from World Bank and OECD database. I run OLS regressing using data analysing software STATA. Basing my assumptions on theoretical knowledge and the way other economics did similar researches I used GDP per Capita, Urbanization Level and Economic Freedom Index as controlling variables, implementing Time and Country Fixed Effects made my empirical model a bit more reliable and satisfying. At the end I got that 1-point increase of tax wedge will result in 0.08-point increase of Illicit activities and results are significant at 5% level.